Efektivitas Program Keluarga Harapan (PKH) dalam Meningkatkan Kesejahteraan Rumah Tangga Miskin di Kabupaten Bekasi - Wahidin Septa Zahran (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to measure the effectiveness of the Family Hope Program (PKH) in improving the welfare of poor households in Bekasi Regency. Using a descriptive qualitative approach, the study focuses on an in-depth understanding of the perceptions and experiences of program beneficiaries. Data was collected through both closed and open-ended questionnaires distributed to 60 respondents, consisting of 50 Beneficiary Families (KPM) and 10 social facilitators. Data analysis was conducted using quantitative descriptive methods for the closed questionnaires, and thematic analysis for the open-ended responses and document study. The results show that more than 75% of respondents felt a positive impact in the field of education, while 72% regularly accessed health services such as Posyandu. Economically, 68% of respondents stated that the PKH assistance helped meet their basic needs, although it was not sufficient for long-term needs. Regarding implementation, 80% of respondents expressed satisfaction with the social facilitation provided, although administrative procedures and limited access in remote areas remain challenges. The conclusion of this study indicates that PKH has a significant social impact on poor households. However, the program’s effectiveness still needs improvement through streamlined administrative processes, adjustment of the aid amount, and greater attention to hard-to-reach areas so that the program’s benefits can be felt more evenly and sustainably.